Draft Genome Sequence of Shiga Toxin-Producing Escherichia coli Strain D92/09 - Da Silva Santos, Ana Carolina [UNESP]; Rodrigues, Josias [UNESP] (Amer Soc Microbiology, 2015)
Escherichia coli is suspected to be involved with Crohn's disease. Adherence and invasion to epithelial cells are properties commonly observed in these bacteria. Here, we present a draft genome sequence of E. coli D92/09, a multidrug-resistant strain, which besides showing these properties produces Shiga cytotoxin-1 and possibly other toxins.